2021
DOI: 10.1186/s12890-020-01383-5
|View full text |Cite
|
Sign up to set email alerts
|

The associations between dietary pattern of chronic obstructive pulmonary disease patients and depression: a cross-sectional study

Abstract: Background Chronic obstructive pulmonary disease (COPD) is a common lung disease during middle age which one of its complications is depression. Depression is considered one of the major causes of severe disability worldwide. One of the factors that affect the severity and incidence of this disease is a lifestyle, especially dietary pattern. On the other hand, some studies showed the relationship between dietary patterns and depression. The present study aims to investigate the dietary patterns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The latest prospective study has revealed that the “balanced dietary pattern” characterized by a high intake of fresh fruit and protein-rich foods (soybeans, meat, poultry, fish or seafood, eggs, and dairy products) is relatively associated with a lower risk of COPD in Chinese adults [ 54 ]. Overall, the evidence concordantly indicated that the dietary intake pattern is an important factor in the pathogenesis and prevention of COPD, involving the relationship between diet and symptoms, lung function, the risk of incidence and progression of COPD, and complications (depression) [ 55 , 56 , 57 , 58 ]. Consistent with the pro-inflammatory effects of a Westernized diet on the airways, we show that a higher DII is significantly associated with lower FEV 1 and FVC among individuals with early COPD in NHANES.…”
Section: Discussionmentioning
confidence: 99%
“…The latest prospective study has revealed that the “balanced dietary pattern” characterized by a high intake of fresh fruit and protein-rich foods (soybeans, meat, poultry, fish or seafood, eggs, and dairy products) is relatively associated with a lower risk of COPD in Chinese adults [ 54 ]. Overall, the evidence concordantly indicated that the dietary intake pattern is an important factor in the pathogenesis and prevention of COPD, involving the relationship between diet and symptoms, lung function, the risk of incidence and progression of COPD, and complications (depression) [ 55 , 56 , 57 , 58 ]. Consistent with the pro-inflammatory effects of a Westernized diet on the airways, we show that a higher DII is significantly associated with lower FEV 1 and FVC among individuals with early COPD in NHANES.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the molecular structure, IL-1 can be subdivided into IL-1 α and IL-1 β , of which IL-1 β is closely related to autoinflammatory and autoimmune diseases and can act with the coreceptor IL-1RacP to form a complex, activate the MAPK signaling pathway within target cells, and induce inflammatory factors expression [ 21 ]. Reports have shown that IL-1 β in COPD patients presented in an aggregated state, whereas blockade of IL-1 β could alleviate the clinical symptoms of patients [ 22 ], indicating that IL-1 β can affect patient outcomes. In this study, the 30 d follow-up results showed 220 surviving patients and 20 dead patients, and patients with different outcomes had obviously varied IL-1 β levels, with AUC (95%CI) = 0.7165 (0.6080-0.8250) for this indicator to predict prognosis, confirming that IL-1 β is associated with patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…All of these factors are relevant to functional limitation of people. Therefore, the sociodemographic and health-related behaviors variation over time can impact on prevalence of CMDs, functional limitation and diet quality among individuals with COPD [ 42 ]. To the best of our knowledge, this study is the first in COPD patients living in Spain to measure and analyze the presence of CMDs, functional limitations, diet quality and gender-related factors at the same time.…”
Section: Introductionmentioning
confidence: 99%